“EFFECTIVE WAYS OF USING PICTURES IN TEACHING GRAMMAR FOR YOUNG LEARNERS” (American Journal of Pedagogical and Educational Research, 2024)
This article is written about the impact of utilizing images in teaching grammar to children. Drawing on research and pedagogical practices, this paper discusses the benefits of incorporating visual aids in grammar instruction and provides practical strategies for integrating pictures into language teaching. The article emphasizes the importance of visual stimuli in enhancing young learners' understanding and retention of grammar concepts, as well as promoting engagement and motivation in the language learning process. This article is shown some engaging picture-based activities for teaching grammar to young learners.